Résilience d’un quartier populaire : enjeux d’un community management territorial - Cyril Masselot (Communiquer)
In this article, we question the design of the animation of a Facebook page on the theme of sustainable consumption in a popular area. We observe the influence of community management as recommended today on presupposed process of appropriation by the inhabitants, and are looking to understand the communications issues of policy dissemination of community management to these people. The various co-building sessions of community management of this experimental communicative device were recorded and transcribed. The speech analysis methods have been enhanced by the use of software Iramuteq. We then get specific speech patterns that include semantic isotopies: they reveal the need for an ingrown local roots, to resort to theories of change management, to incorporate animation in an innovative complex system, and not to forget the public who are not yet aware of the eco-behaviour. These assessments allow to imagine how to take into account the issues of community management in this specific context.